Self-Selection at the Candidate Level of Simultaneous Interpreting - Kapranov, Oleksandr (East European Journal of Psycholinguistics, 2015)
This article aims at outlining the role of self-selection in the decision by the potential students of simultaneous interpreting, i.e. interpreter candidates, to apply for a university programme in simultaneous interpreting. The role of self-selection is investigated by means of a psycholinguistic experiment involving the potential students’ written reflections on the topic ‘Why I Chose to Apply for a University Programme in Simultaneous Interpreting’. The experiment is conducted with six interpreter candidates (further referred to as ‘participants’) who want to apply for university translation and interpreting programmes at Stockholm University (Sweden), Brussels Free University (Belgium) and University of Seville (Spain) respectively. The study’s specific objective is to identify main categories involved in the participants’ self-selection of the university programme in simultaneous interpreting. The participants are instructed to write a 500 words essay on the topic ‘Why I Chose to Apply for a University Programme in Simultaneous Interpreting’. The corpus of the participants’ essays is subsequently tagged in computer program CLAN in order to facilitate the identification of the self-selection categories. Data analysis reveals that the most frequent categories involved in self-selection are ‘Interest’, ‘Communication with other people’, ‘Another identity’, ‘Novelty’ and ‘Interpreting as a natural choice’ respectively. References Albl-Mikasa, M. (2013). ELF speakers’ restricted power of expression: Implications for interpreters’ processing. Translation and Interpreting Studies, 8(2), 191–210. Barik, H. C. (1975). Simultaneous interpretation: Qualitative and linguistic data. Language and speech, 18(3), 272–297. Bellman, S., & Varan, D. (2012). Modeling Self-Selection Bias in InteractiveCommunications Research. Communication Methods and Measures, 6(3), 163–189. Bolaños-Medina, A. (2014). Self-efficacy in translation. Translation and Interpreting Studies, 9(2), 197–218. Dam, H. V., & Zethsen, K. K. (2013). Conference interpreters—the stars of the translation profession?: A study of the occupational status of Danish EU interpreters as compared to Danish EU translators. Interpreting, 15(2), 229–259. De Bot, K. (2000). Simultaneous interpreting as language production. BENJAMINS TRANSLATION LIBRARY, 40, 65–88. Gile, D. (1999). Testing the Effort Models’ tightrope hypothesis in simultaneous interpreting-A contribution. Hermes, 23(1999), 153–172. Goldman-Eisler, F. (1972). Segmentation of input in simultaneous translation. Journal of Psycholinguistic Research, 1(2), 127–140. House, J. (2013). Towards a new linguistic-cognitive orientation in translation studies. Target, 25(1), 46–60. Ivars, A. J., & Calatayud, D. P. (2013). Mindfulness training for interpreting students. Lebende Sprachen, 58(2), 341–365. Kapranov, A., Kirsner, K., Dunn, J., & Hird, K. (2008). Simultaneous interpreting as a complex dynamic system: An approach to its measurement. In G. T. Polenova & O. E. Bondarets (Eds.), Collected articles of the IInd international linguistics conference (Taganrog, Russia) pp. 256– 278. Newcastle upon Tyne, Cambridge Scholars Publishing. Kapranov, A., & Vik-Tuovinen, G.-V. (2008). Flyt vid simultantolkning hos informanter på olika nivåer av professionalitet. Käännösteoria, ammattikielet ja monikielisyys. VAKKI:n julkaisut, 35, 56–66. Kapranov, A. (2009). Pauses in Simultaneous Interpreting from/into Norwegian Performed by the Students of Norwegian as a Third Language. Nordand. Nordisk Tidsskrift for Anderspråksforskning, 1, 53–66. Kapranov, A. (2012). Swedish University Students’ Perception of English as a Global Language. In "Kalbos, kultūra ir globalizacija", (pp. 8–14). Vilnius: Mykola Romeris University. Kapranov, O. (2014). Self-Selection of a Course in Psycholinguistics. East European Journal of Psycholinguistics, 2, 75–82. Kenrick, D. T., Li, N. P., & Butner, J. (2003). Dynamical evolutionary psychology: individual decision rules and emergent social norms. Psychological review, 110(1), 3. Kurz, I. (2003). Physiological stress during simultaneous interpreting: a comparison of experts and novices. The Interpreters’ Newsletter, 12, 51–67. Mackintosh, J. (1999). Interpreters are made not born. Interpreting, 4,(1), 67–80. Macnamara, B.N., Moore A.B., Kegl, J.A. & Conway, A.R. (2011). Domain-general cognitive abilities and simultaneous interpreting skills. Interpreting, 13,1, 121–142. Malakoff, M. E. (1992). Translation ability: A natural bilingual and metalinguistic skill. Advances in psychology, 83, 515–529. Moser-Mercer, B. (2000). Simultaneous interpreting: Cognitive potential and limitations. Interpreting, 5(2), 83–94. Pike, G. R. (2011). Using college students’ self‐reported learning outcomes in scholarly research. New directions for institutional research, 2011(150), 41–58. Pulkka, A. T., & Niemivirta, M. (2013). Predictive relationships between adult students’ achievement goal orientations, course evaluations, and performance. International Journal of Educational Research, 61, 26–37 Rosiers, A., Eyckmans, J. & Bauwens, D. (2011). A story of attitudes and aptitudes? Investigating individual difference variables within the context of interpreting. Interpreting 13, 1, 53– 69. Russo, M. (2011). Aptitude testing over the years. Interpreting, 13, 1, 5–30. Ryan, A., Ployhart, R. E., Greguras, G. J., & Schmit, M. J. (1998). Test Preparation Programs in Selection Contexts: Self‐Selection and Program Effectiveness. Personnel Psychology, 51(3), 599–621. Seeber, K. (2013). Cognitive load in simultaneous interpreting. Target, 25, 1, 18–32. Shlesinger, M. & Pöchhacker, F. (2011). Aptitude for interpreting. Interpreting, 13,1, 1–4. Takeda, K. (2010). What interpreting teachers can learn from students: a case study. Translation & Interpreting, 2(1), 38–47. Timarová, Š., & Salaets, H. (2011). Learning styles, motivation and cognitive flexibility in interpreter training. Self-selection and aptitude. Interpreting, 13,1, 31–52. Zwischenberger, C. (2009). Conference interpreters and their self-representation. A worldwide web-based survey. Translation and interpreting studies, 4(2), 239–253.